Exploring the relationship between different types of reference group influence and young consumers' health tourism intention - Caisheng Liao; Yang Lin; Zhao Li; Xinze Zhan (Social Sciences and Humanities Open, 2023)
Despite the many achievements in health tourism, relatively few studies conducted on the health tourism consumption decisions of young consumers. This study primarily investigates how different types of reference group influence affect young consumers' health tourism intentions. Based on the theoretical framework of Stimuli-Organism-Response (SOR), a mediation model including perceived value was constructed and structural equation modeling was used to analyze the relationship between the types of reference group influence, perceived value, and health tourism intention. The results showed that both informational influence and utilitarian influence in the reference group influence have a positive impact on health tourism intention. Of these, informational influence is greater. Secondly, perceived value also has a positive effect on consumers' health tourism intention and plays a mediating role between the reference group influence and the health tourism intention. The findings contribute to our understanding of the impact of different types of reference group influence on health tourism intentions and enrich the application of SOR theory. The findings have implications for promoting healthy tourism consumption among young consumers.